Digital spillovers and SMEs’ performance in Sub-Saharan Africa - (:unkn) unknown (My University, 2020)
In this policy brief, we use survey data from the WBES to provide an empirical assessment of the contribution of digital technologies diffusion to African SMEs’ performance. Compared to existing empirical evidence on the impacts of digital technologies on African firms, the quantitative analysis hereafter presented incorporates various novelties.
Keywords: African Research